Linguistic representation of the linguocultural concept «loneliness» in Russian love lyrics (Eurasian Journal of Philology Science and Education, 2016)
The article discusses the concept of artistic expression of «loneliness» in Russian love lyrics. The analysis of literary texts by identifying features of the conceptual system of a writer enables to describe the integral part of the collective, national experience of the world cognition. The paper determines the conceptual core of the concept of «loneliness», which is characterized by such basic features as ‘separate from other similar, having no family, relatives, without like-minded people, colleagues’.It is noted that individual, textual component of the concept of «loneliness» is characterized by negative connotation imagery: silence, silence, gloom, emptiness, sleep, extinction of life and death.The emotional field of the concept, formed on the basis of the analysis of works of Russian classical poetic texts, shows that loneliness for the Russian people is an absolute evil and therefore it is defined by adjectives in which this feature is manifested to a maximum extent: perfect, complete, absolute, unbearable.
Keywords: concept; loneliness; imagery; artistic expression.